Global patterns of healthy life expectancy in the year 2002 - Chatterji Somnath; Tandon Ajay; Salomon Joshua A; Iburg Kim; Mathers Colin D; Ustün Bedirhan; Murray Christopher JL (BMC, 2004)
Abstract Background Healthy life expectancy - sometimes called health-adjusted life expectancy (HALE) - is a form of health expectancy indicator that extends measures of life expectancy to account for the distribution of health states in the population. The World Health Organization reports on healthy life expectancy for 192 WHO Member States. This paper describes variation in average levels of population health across these countries and by sex for the year 2002. Methods Mortality was analysed for 192 countries and disability from 135 causes assessed for 17 regions of the world. Health surveys in 61 countries were analyzed using new methods to improve the comparability of self-report data. Results Healthy life expectancy at birth ranged from 40 years for males in Africa to over 70 years for females in developed countries in 2002. The equivalent "lost" healthy years ranged from 15% of total life expectancy at birth in Africa to 8-9% in developed countries. Conclusion People living in poor countries not only face lower life expectancies than those in richer countries but also live a higher proportion of their lives in poor health.